Intervenção mediacional na aprendizagem do braille: um estudo com crianças deficientes visuais - Dionísio, Ana Maria Pereira (2016)
This study aimed to construct and evaluate a proposed mediational intervention with preschool children through reading workshops and writing in Braille system. The proposal is based on the concepts of Vygotsky on defectology and approach to the Mediated Learning Experience (MLE) developed by Feuerstein. For the research were drawn up ten Mediational workshops, in which they developed a work by reading a children's story and from her reading activities and writing in Braille system. The workshops took place within in kindergarten room of the institution. Study participants were four blind children, six and seven years in an institution that assists visually impaired people in the city of Uberaba / MG, and their mothers and the teacher responsible for the room in which they study. During the workshops, the children showed interest in participating in the activities of reading and writing in Braille. We believe that the data built during the research are not sufficient to establish a generalization, due to the small number of participants. However, at the end of the workshops and the assessment of participants' responses can infer the relevance of the proposal, because in addition to the interest shown and the request of the children there were more activities like that, it was noticed greater fluency in reading and greater ease in writing.